Multidisciplinary treatment for hilar and intrahepatic cholangiocarcinoma: A review of the general principles. (October 2020) - Sapisochin, Gonzalo; Ivanics, Tommy; Subramanian, Vijay; Doyle, Majella; Heimbach, Julie K.; Hong, Johnny C.
Abstract: Cholangiocarcinoma (CCA) is a rare but devastating malignancy that presents late, and associated with a high mortality if untreated. CCA is locally aggressive and located in close proximity to vital structures i.e. the portal vein and hepatic artery. A complete extirpation of the tumor including microscopically detectable disease R0 resection offers the best possibility of long-term survival in patients with CCA. As such, the surgical approach to achieve a R0 resection is dictated by the location of the tumor and the presence of underlying liver disease. The present article focuses on the general principles of the multidisciplinary treatment of hilar and intrahepatic CCA. Highlights: Hilar and intrahepatic cholangiocarcinoma are rare but devastating malignancy. R0 resection is the definitive treatment for hilar and intrahepatic cholangiocarcinoma. Surgical resection is the first line of treatment for resectable hilar and intrahepatic cholangiocarcinoma. Neoadjuvant therapy and liver transplantation provide survival benefits in select unresectable hilar and intrahepatic cholangiocarcinoma.